2022
DOI: 10.3389/fmats.2022.1057128
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of fiber-reinforced concrete produced with steel fibers extracted from waste tire

Abstract: With the increasing number of vehicles in the world, the amount of waste tires is increasing day by day. In this case, the disposal of expired tires will cause serious environmental problems. In recent years, instead of disposing of tire wastes, most of them have been started to be recycled to produce fiber-reinforced concrete. Thus, steel fibers recovered from waste tires have been preferred as an alternative to industrial steel fibers due to their environmentally friendly and low-cost advantages. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“…Similar results were also reported on a study by Elik et al 45 investigating the performance assessment of fiber‐reinforced concrete produced with waste lathe fibers. Zeybek et al 46 carried out experimental investigations to evaluate the performance of concrete reinforced with steel fibers extracted from waste tires with volume fractions 1%, 2%, and 3% (with compression, splitting tensile, and flexure tests carried out). It was found that the mechanical properties were improved with the addition of fibers; however, workability was significantly reduced with the addition of more than 2% volume fraction of fibers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar results were also reported on a study by Elik et al 45 investigating the performance assessment of fiber‐reinforced concrete produced with waste lathe fibers. Zeybek et al 46 carried out experimental investigations to evaluate the performance of concrete reinforced with steel fibers extracted from waste tires with volume fractions 1%, 2%, and 3% (with compression, splitting tensile, and flexure tests carried out). It was found that the mechanical properties were improved with the addition of fibers; however, workability was significantly reduced with the addition of more than 2% volume fraction of fibers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Concrete is the most widely used building material in the world due to its many advantages over other materials [1]. Concrete consists of various ingredients, including cement, aggregates (fine and coarse), water, and some additives, and it is widely used as a building material in civil engineering applications such as dams, bridges, and roads [2]. Compressive strength is the most fundamental of the different indices of concrete qualities since it is directly related to structural safety and is essential in the performance measurement of structures throughout their entire life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…To date, numerous researchers are studying the use of recycled fibers obtained from tires for concrete reinforcement [ 19 , 20 , 21 ] and presented numerous interesting conclusions. With the state of the economy of used tires at present, there remains a problem related to the rational management of waste, which is steel fiber.…”
Section: Introductionmentioning
confidence: 99%